Maternal and Child Health Out-of-Pocket Expenditure and Service Readiness in Lao PDR : Evidence for the National Free Maternal and Child Health Policy from a Household and Health Center Survey (2013 Update) - World Bank Group (World Bank, Washington, DC, 2016)
Lao PDR has made notable progress in improving maternal health, with mater¬nal mortality decreasing from 1,600 per 100,000 births in 1990 to 220 in 2013.1 However, in order for further gains to be realized, at least two barriers need to be addressed – the low utilization of maternal health (MH) services and weak financial protection, especially among the lower wealth quintiles, in order to improve the level and equity of maternal health. In order to address these financial barriers, the Government of Lao PDR introduced a national free maternal and child health (MCH) policy. Although there were geographic variations in the operationalization of this policy,4 the essence is that user fees paid OOP by pregnant women or for children under-five were replaced with case-based payments paid by or through the government or donors, for essential MCH services. In addition, small cash payments were provided to patients to cover opportunity and transport costs. This report summarizes key findings from two household, village, and health center surveys in southern and rural Lao PDR conducted in 2010 and 2013, providing for the first time in Lao PDR, large-scale household-level data on OOP expenditure for MCH-specific services.